Cracks in Coverage: U.S. Measles Outbreak 2024-25 - Jasmit Kaur Puri; Jay Rajiv Shinde; Nipurna Gawali; Srushti Moreshwer Patil; Saloni Gajakos, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The 2024–25 measles outbreak in the United States marks the largest resurgence since the disease was declared eliminated in 2000. With over 1,000 confirmed cases across 25 states— primarily centered in Texas—this outbreak highlights critical vulnerabilities in national immunization infrastructure. This narrative review synthesizes recent data from the Centers for Disease Control and Prevention (CDC), peer-reviewed studies, and risk models to examine the multifactorial drivers of the outbreak. Vaccine hesitancy, inconsistent state-level exemption policies, reduced MMR coverage, and delays in outbreak detection collectively contributed to sustained transmission. Approximately 92% of confirmed cases were unvaccinated or undervaccinated, with rising rates of nonmedical exemptions concentrated in politically permissive jurisdictions. Despite improved federal surge response, actions remained largely reactive. Realtime modeling, culturally informed communication, and closure of exemption loopholes are essential to reestablish herd immunity. The resurgence of measles in a post-elimination setting underscores the need for renewed public health vigilance, national policy harmonization, and sustained community engagement to prevent future vaccine-preventable disease outbreaks.